The Role of Social Sciences in Human Life - M Husin; Hafidh Maksum; Adnan Adnan; Israwati Israwati; Said Darnius (Proceedings of AICS - Social Sciences, 2021)
The function of social sciences, which Bung-Hatta described as having an academic enterprise and applied science, in this country's chaotic national situation cannot be separated. The social sciences play a significant impact in determining and advancing humanity's history. The nature of social science as an academic enterprise requires it to attempt not only the discourse about what happened but also what should happen. The social sciences have a critical role in the prevention, application, and prediction of human issues. But this is possible if the social sciences work together synergistically to complement one another.Keywords: Social Science, Human Life.